125k views
0 votes
Multiple the following:

1.) (-3x)(3x)
2.) (4x)²
3.) x (x+4)
4.) (x+2)²
5.) (x+3)(x-4)
6.) x² (x²+2x-4)​

2 Answers

5 votes
1) (-3x)(3x)

= -9x^2

2) (4x)^2 = 4^2 x^2

= 16x^2

3) x(x+4) = x•x+4x

= x^2+4x

4) (x+2)^2 = x^2+2x•2+2^2

= x^2+4x+4

5) (x+3)(x-4) = x^2-4x+3x-12

= x^2-x-12

6) x^2(x^2+2x-4) = x^2•x^2•x^2•2x-4x^2

= x^4+2x^3-4x^2
User Rohit Chopra
by
5.7k points
2 votes

Answer:

1.-9x^2

2.16x^4

3.x^2+4x

4.x^2+4x+4

5.x^2-x-12

6.x^4+2x^3-4x^2

Explanation:

User Steve Ruben
by
5.3k points